Adsorption of Catalase Enzyme on Silica Gel - ALKAN, SALIH (Asian Journal of Chemistry, 2010)
Immobilization of catalase enzyme on fibrous silica gel was investigated in present study. Simple adsorption has no effect on enzyme activity and appeared to as a new method of immobilizing the enzyme at high ionic strength. The storage stability and the kinetic parameters of immobilized enzyme and its activity were evaluated under varied pH, ionic strength and temperature. These studies indicate that silica gel is a valuable support for simple adsorption of enzymes.